Tales and Novels of J. de La Fontaine $1 (BVolume 07s - La Fontaine, Jean de, 1621-1695 (Salt Lake City, UT : Project Gutenberg, 2004)
"Tales and Novels of J. de La Fontaine $1 (BVolume 07" by Jean de La Fontaine is a collection of fables and tales written during the 17th century, specifically in the context of the literary and cultural milieu of classical France. This work delves into themes of love, desire, and the folly of human behavior through creatively woven narratives that often include moral lessons. La Fontaine's writing, rich with allegorical significance, presents a reflection on human nature and societal norms. The volume features two key tales: "The Falcon" and "The Little Dog." In "The Falcon," a young man named Frederick, deeply infatuated with a beautiful woman named Clytia, squanders his wealth in attempts to win her affection, ultimately leaving him destitute and heartbroken. After the death of Clytia's husband, she begins to realize Frederick's devotion, especially when he sacrifices his last possessions for her son's well-being. Conversely, "The Little Dog" tells the story of a jealous judge, Anselm, who fears for his young and beautiful wife's fidelity. He sends her away and seeks to guard her when he's away, but she is pursued by a clever suitor, Atis, who, with the aid of a magic dog, exploits the judicial couple's trust while highlighting the folly of jealousy and the nature of desires. Through these narratives, La Fontaine expertly illustrates the complexities of love and the absurdities that often accompany it. (This is an automatically generated summary.)s
The Falcon -- The Little Dog.
Release date is 2004-03-01
This eBook was produced by David Widger
Keywords: French poetry -- Translations into English; Fables, French -- Translations into English